"Some Safe Way of Dying": A Literary Study of Suicide in 1940s Britain - BRADY, WILLIAM JOSEPH (Trinity College Dublin. School of English. Discipline of English, 2019)
The hitherto unimaginable challenges, dilemmas and paradoxes of the Second World War and its immediate aftermath were, this thesis contends, mediated through a language and imaginative framework of suicide in British literature. Suicide, in the words of diarist and Bloomsbury affiliate, Frances Partridge, constituted the ultimate beacon of individual self-determination, providing a last refuge of self-deliverance from the tumultuous socio-political shifts of the decade and presenting in essence 'some safe way of dying'. Responding to the ordeal of living within a climate of 'total war', many writers of the forties drew on the concept of self-annihilation as a source of consolation, of social critique and as a means of articulating the otherwise inexpressible crises of war, post-war and identity. Moreover, the concept of suicide may also be seen to perform a normative regulatory function within some areas of war writing, defining public conceptions of courage, cowardice, duty and transgression. Drawing on the four typologies of suicide outlined by the sociologist, Émile Durkheim, this thesis investigates the ways in which British fiction of the 1940s fixates on and actively utilises suicide and suicidality. In so doing, it uncovers how and why the destabilisation of public and private spheres, the experience of the collective regimentation of body and mind, and the anticipatory ordeals of aerial combat all find expression through a language of self-destruction. Building on established and recent cultural scholarship of Britain in the Second World War and immediate post-war and engaging with the emerging field of literary suicidology, I examine how the suicidal obsession of 1940s Britain is mobilised within the literature of the decade to bolster and disrupt the hegemonic discourses and myths of the period.
APPROVED
Keywords: 1940s; Second World War; Suicide; Durkheim; Trauma; Postwar Literature